# Solve for z -8+4(-4z-5)=-2(7z+7)-5

-8+4(-4z-5)=-2(7z+7)-5
Simplify -8+4(-4z-5).
Simplify each term.
Apply the distributive property.
-8+4(-4z)+4⋅-5=-2(7z+7)-5
Multiply -4 by 4.
-8-16z+4⋅-5=-2(7z+7)-5
Multiply 4 by -5.
-8-16z-20=-2(7z+7)-5
-8-16z-20=-2(7z+7)-5
Subtract 20 from -8.
-16z-28=-2(7z+7)-5
-16z-28=-2(7z+7)-5
Simplify -2(7z+7)-5.
Simplify each term.
Apply the distributive property.
-16z-28=-2(7z)-2⋅7-5
Multiply 7 by -2.
-16z-28=-14z-2⋅7-5
Multiply -2 by 7.
-16z-28=-14z-14-5
-16z-28=-14z-14-5
Subtract 5 from -14.
-16z-28=-14z-19
-16z-28=-14z-19
Move all terms containing z to the left side of the equation.
Add 14z to both sides of the equation.
-16z-28+14z=-19
-2z-28=-19
-2z-28=-19
Move all terms not containing z to the right side of the equation.
Add 28 to both sides of the equation.
-2z=-19+28
-2z=9
-2z=9
Divide each term by -2 and simplify.
Divide each term in -2z=9 by -2.
-2z-2=9-2
Cancel the common factor of -2.
Cancel the common factor.
-2z-2=9-2
Divide z by 1.
z=9-2
z=9-2
Move the negative in front of the fraction.
z=-92
z=-92
The result can be shown in multiple forms.
Exact Form:
z=-92
Decimal Form:
z=-4.5
Mixed Number Form:
z=-412
Solve for z -8+4(-4z-5)=-2(7z+7)-5

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top